2004
DOI: 10.2300/acari.13.57
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Ecology of Astigmatid Mites LXXIII. Neral as an Alarm Pheromone of the Acarid Mite, Oulenzia sp. (Astigmata: Winterschmidtiidae)

Abstract: Hexane extracts derived from an unidentified Oulenzia sp. showed the alarm pheromone activity. The extract was composed of the following 10 compounds; tridecane, neral, pentadecane, dodecane, 3-hydroxybenzene-1,2-dicarbaldehyde, geranial, (Z)-7-pentadecene and 7-hydroxyphthalide in decreasing order together with two unknown compounds. After fractionation with a silica gel column, the active fraction consisted of a mixture of neral and geranial. Neral was found to show the activity, but geranial was not. Neral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Citral consists of two isomers, neral and geranial, and the mass spectra of these two compounds are quite similar. However, retention times are different on an HP5-ms column and geranial elutes after neral (Shimizu et al 2004). We concluded that compound I was geranial which is also a pheromone component in a wide variety of species, among others the Ambrosia beetle Platypus koryoensis (Kim et al 2009).…”
Section: Analysis Of Collected Volatilesmentioning
confidence: 85%
“…Citral consists of two isomers, neral and geranial, and the mass spectra of these two compounds are quite similar. However, retention times are different on an HP5-ms column and geranial elutes after neral (Shimizu et al 2004). We concluded that compound I was geranial which is also a pheromone component in a wide variety of species, among others the Ambrosia beetle Platypus koryoensis (Kim et al 2009).…”
Section: Analysis Of Collected Volatilesmentioning
confidence: 85%
“…It is present in 35 of 60 species of astigmatid mites examined, including 28 unidentified species [2]. Neral has been identified as the alarm pheromone in six mite species, including Carpoglyphus lactis [3–7]. This compound was also identified as the aggregation pheromone of Schwiebea elongata [8] and as the sex pheromone of Histiogaster sp.…”
mentioning
confidence: 99%
“…Neral [(Z)-3,7-dimethyl-2,6-octadienal] is a geometric isomer from citral and works as an alarm pheromone of C. lactis (Kuwahara et al, 1980) as well as for other astigmatic strains (Shimizu et al, 2004). This compound with lemon-like aroma has also been associated with reproductive and aggregation pheromones in other strains (Nishimura et al, 2002); it thus plays an important role in the semiochemical communications of astigmatic strains.…”
Section: Norisoprenoidsmentioning
confidence: 99%